On Enhanced Cooperation - Massimo Bordignon; Sandro Brusco (Center for Economic Studies and ifo Institute (CESifo), 2003)
Should a subset of member states of a federation be allowed to form a sub-union on some policy issue? When centralization is not politically feasible, allowing an enhanced cooperation agreement among a subset of countries permits the latter to gain benefits which would otherwise be lost. However, if in the future the excluded countries also want to join, the fact that a sub-union has been formed in the past may change the status quo to the advantage of the first comers. We show that as long as countries can commit to harmonize at a policy which also takes into account the utility of the excluded country, sub-union formation may be optimal. The relative advantage of a sub-union towards centralization increases when transfers are costly. On the other hand, if commitment is not possible then excluded countries may be penalized. We use these results to discuss of the newly introduced rules for enhanced cooperation agreements in the European Union, suggesting that they might lead to increased centralization.
Keywords: 330; international unions; fiscal federalism; treaty of Nice; corporate taxation